1995
DOI: 10.1093/infdis/172.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nasopharyngeal Colonization with Nontypeable Haemophilus influenzae in the First 2 Years of Life

Abstract: Two hundred children were followed from birth through 2 years of age with nasopharyngeal cultures to determine the normal colonization pattern of nontypeable Haemophilus influenzae. Forty-four percent of the children were colonized on one or more occasions; the acquisition rate was greatest in the first year. Monthly prevalence rates were 11%. Colonization with the initial strain persisted 1-5 months (median, 2). Children carried 1 predominant strain at a time but became colonized with up to 7 different strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
103
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 8 publications
9
103
1
8
Order By: Relevance
“…When sequential NTHi NP colonization was observed at different time points in a child, different STs were involved. Faden et al (1995) found that NTHi strains cleared the NP in ,3 months in 90 % of the children they studied. We did not observe any reacquisition of previously carried NTHi strains, similar to previous studies by Spinola et al (1986) and Faden et al (1995).…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…When sequential NTHi NP colonization was observed at different time points in a child, different STs were involved. Faden et al (1995) found that NTHi strains cleared the NP in ,3 months in 90 % of the children they studied. We did not observe any reacquisition of previously carried NTHi strains, similar to previous studies by Spinola et al (1986) and Faden et al (1995).…”
mentioning
confidence: 84%
“…Faden et al (1995) found that NTHi strains cleared the NP in ,3 months in 90 % of the children they studied. We did not observe any reacquisition of previously carried NTHi strains, similar to previous studies by Spinola et al (1986) and Faden et al (1995).Prolonged colonization of NTHi strains (.3 months) was observed in~25 % of the 33 children where NTHi colonization was observed more than once. ST146 and ST685 belong to the same clonal complex and have no predictor founder.…”
mentioning
confidence: 84%
See 3 more Smart Citations